Trim71 Links an Ancient MicroRNA Pathway to Neural Stem Cell Development and Human Congenital Hydrocephalus. (1st September 2019) - Phan, Duy; Foster, Daniel; Jux, Bettina; Lake, Evelyn; Constable, Todd; Kolanus, Waldemar; Slack, Frank; Kahle, Kristopher T
Abstract: INTRODUCTION: Congenital hydrocephalus (CH), the most common brain malformation that affects 1:1000 live births, remains poorly treated owing to incomplete understanding of disease pathogenesis. Identification of novel CH disease genes is a powerful approach to understanding the molecular genetics of CH. Whole exome sequencing in humans has identified TRIM71 as a bona fide CH disease gene. Trim71 is the major target of the ancient let-7 pathway that famously regulates cell differentiation and organismal development via microRNA-mediated gene silencing in Caenorhabditis elegans . Previous works have implicated Trim71 in the regulation of embryonic neural stem cell (NSC) fate, yet its cellular and molecular function in NSCs remain poorly understood. METHODS: To gain a better understanding of Trim71 as a paradigm of NSC involvement in CH, we have generated a mouse model that harbors the point mutation in Trim71 that results in human CH (R595H) using CRISPR-Cas9. RESULTS: We found that a subset of mice heterozygous for the Trim71 R595H mutant allele developed severe communicating hydrocephalus with accompanying macrocephaly by 4 wk of age. CONCLUSION: Investigation into the function of Trim71 and its CH-causing mutations using our novel mouse models presents outstanding opportunities to increase understanding of human NSC regulation, brain development, and CH pathogenesis.